Manual de procesos contratación de personal, subprocesos: reclutamiento, selección e inducción para la unidad de Talento Humano de la Dirección Distrital 11D02 Catamayo Chaguarpamba Olmedo-Educación, año 2022. - Encarnación Villalta, Alan Steven (2022)
The present research work consisted in the formalization of the process of Personnel Recruitment Subprocesses: Recruitment, Selection and Induction for the Human Resources Unit of the District Directorate 11D02 Catamayo Chaguarpamba Olmedo-Education, which allowed establishing the appropriate guidelines for the aforementioned process achieving an efficient and effective quality management that reflects organized administrative processes and ensure that the final result is the best. For the development of the present work, the methodology used for the elaboration of the research proposal and, therefore, the formalization of the process was directed to the application of information gathering instruments (semi-structured interview and observation sheet) that provided pertinent information of the process, through the type of research, it was possible to establish the SWOT tool for the elaboration of the Situational Diagnosis and the methodology for the survey of UNL processes elaborated by the Public Administration Career for the construction of the manual proposal of the process with the support of the analytical and synthetic method, analyze the results and the action research to provide a solution to the problem, to later validate the information and socialize the proposal. Ultimately, the results, discussion, conclusions and recommendations of the research are shown, as well as the theory that supports them, ending with the approval and delivery of the proposal of the manual of the Recruitment process Subprocesses: Recruitment, Selection and Induction. It should be emphasized that this proposal will help to strengthen the Human Resources Unit, keeping an updated record of the Recruitment process together with its sub-processes.